2012
DOI: 10.1111/j.1540-6261.2011.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Disclosure and Corporate Governance

Abstract: Public policy discussions typically favor greater corporate disclosure as a way to reduce firms' agency problems. This argument is incomplete because it overlooks that better disclosure regimes can also aggravate agency problems and related costs, including executive compensation. Consequently, a point can exist beyond which additional disclosure decreases firm value. Holding all else equal, we further show that larger firms will adopt stricter disclosure rules than smaller firms and firms with better disclosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
232
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(262 citation statements)
references
References 39 publications
12
232
2
1
Order By: Relevance
“…Dernev, et al (2005) associated a positive link between corporate governance and firm performance. In past various studies suggest an number of ways through which the corporate governance practices can be translated in to improved firm value like in studies by Hermalin, et al (2011). Their study result finding suggest that better price performance is associated with firm that have indicators of high disclose quality, having outside ownership concentration higher and firm which are focused rather that shows diverse.…”
Section: Literature Reviewmentioning
confidence: 57%
“…Dernev, et al (2005) associated a positive link between corporate governance and firm performance. In past various studies suggest an number of ways through which the corporate governance practices can be translated in to improved firm value like in studies by Hermalin, et al (2011). Their study result finding suggest that better price performance is associated with firm that have indicators of high disclose quality, having outside ownership concentration higher and firm which are focused rather that shows diverse.…”
Section: Literature Reviewmentioning
confidence: 57%
“…One possibility is that the poor performance of firms in the 1970s brought about improved board diligence, thereby making the CEO job less secure (Hermalin, 2005). Similarly, enhanced disclosure of financial information may have led to increases in the level of pay to compensate executives for the disutility of stronger monitoring (Hermalin and Weisbach, 2009). These theories are consistent with the increasing fraction of CEOs being hired from outside the firm, the rise in managerial turnover, and the growth in the likelihood of forced departures (Hadlock and Lumer, 1997;Murphy, 1999;Huson, Parrino and Starks, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Pahuja and Bhatia (2010) have found that size of a company is a significant determinant of disclosures and there is a substantial scope for improvement in the corporate governance disclosure practices. All other factors being equal, larger firms will adopt stricter disclosure rules than smaller firms and firms with better disclosure will employ more able management (Hermalin and Weisbach, 2012).…”
Section: Executive Compensationmentioning
confidence: 99%
“…The results indicate that disclosure and timeliness are not significant contributing factors in the relationship between corporate governance and market performance (Haat et al, 2008). Hermalin and Weisbach (2012) stated that public policy discussions typically favour greater corporate disclosure as a way to reduce firms' agency problems. However, better disclosure regimes can also aggravate agency problems and related costs, including executive compensation.…”
Section: Executive Compensationmentioning
confidence: 99%